Acceptance of gig economy as source of halal income among Muslim graduates in Kelantan / Alia Najwa Anuar - Anuar, Alia Najwa (2022)
The issue of job opportunities for graduates today is very important. Good and halal jobs are also very important in the lives of all human beings, especially to Muslim individuals. Gig economy is a job that can be used as a livelihood it is known as partnership economy and literally means an independent job, done as a side job where it can generate income in a short and flexible time. But this problem is associated with the thinking of graduates who think that after graduation they will expect to be accepted to work in permanent jobs either in the private or public sector. This study aims to explore the acceptance of gig economy jobs as one of the sources of halal income among Muslim graduates in Kelantan, examine the types of gig jobs involved by Muslim graduates in Kelantan and identify factors that influenced Muslim graduates to opt the gig-type jobs. The researcher used a qualitative method that is through open-ended question interviews to Muslim graduates in Kelantan. This research has found that the majority of respondents have knowledge related to gig economy jobs but there are also some respondents who do lacked understanding it, less efficient in identifying halal jobs where the income earned is avoided from prohibition, especially in transactions and so on. Finally, there are some recommendations related to the deeper acceptance of gig economy as halal income without involving illegal elements and hope that this study can provide a positive view on gig jobs as a halal source of income in the lives of Muslims.